2017
DOI: 10.1021/acs.biochem.6b00912
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Ligation of the N-Terminal Amine of HypA Is Required for Urease Maturation in Helicobacter pylori

Abstract: The human pathogen Helicobacter pylori requires nickel for colonization of the acidic environment of the stomach. HypA, a Ni metallochaperone that is typically associated with hydrogenase maturation, is also required for urease maturation and acid survival of H. pylori. There are two proposed Ni site structures for HypA; one is a paramagnetic 6-coordinate site characterized by X-ray absorption spectroscopy (XAS) in unmodified HypA while another is a diamagnetic four-coordinate planar site characterized by solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(87 citation statements)
references
References 55 publications
7
80
0
Order By: Relevance
“…An optimal balance between nickel uptake and incorporation in metalloenzymes is essential for gastric colonization by H. pylori . Nickel binding is required at the N‐terminal NHE motif of the Ni‐metallochaperone HypA, involved in urease and [NiFe] hydrogenase maturation, which are essential for acid survival of H. pylori . Fischer et al .…”
Section: Helicobacter Pylori Gastric Colonization and Acid Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…An optimal balance between nickel uptake and incorporation in metalloenzymes is essential for gastric colonization by H. pylori . Nickel binding is required at the N‐terminal NHE motif of the Ni‐metallochaperone HypA, involved in urease and [NiFe] hydrogenase maturation, which are essential for acid survival of H. pylori . Fischer et al .…”
Section: Helicobacter Pylori Gastric Colonization and Acid Resistancementioning
confidence: 99%
“…Nickel binding is required at the N-terminal NHE motif of the Ni-metallochaperone HypA, involved in urease and [NiFe] hydrogenase maturation, which are essential for acid survival of H. pylori. 8 Fischer et al 9 identified a novel H. pylori nickel transport system NiuBDE. NiuBDE is required for nickel-dependent urease activation and acid survival.…”
Section: Nickel Is Essential For Gastric Colonization By H Pylorimentioning
confidence: 99%
“…The HypA structures reveal that the nickel binding site and the zinc binding site are separated by a long flexible linker (Figures 8 and 9) [98][99][100]. The N-terminal nickel site features a highly conserved MHE motif, which includes the first three amino acids at the N-terminus of the protein, that is used to bind two Ni(II) ions per dimer with micromolar affinity [93][94][95][96]98,101]. A K d of 75 ± 46 nM was reported by Douglas et al for a Strep-tagged HypA protein binding to nickel in competition with a well-established metal binding indicator, Mag-fura 2 [102].…”
Section: Hypamentioning
confidence: 99%
“…HypA utilizes two conserved CXXC motifs to bind one zinc ion per monomer [93,94,[97][98][99][100][101] with nanomolar affinity [94]. HypA proteins have been reported as being a dimer in solution based on elution volumes [94,95], however, size exclusion chromatography in combination with multiple light scattering (SEC-MALS) determined that the protein is a monomer in solution [96]. HypA proteins feature two metal binding sites, a N-terminal nickel site and a zinc site [94,95,[97][98][99][100].…”
Section: Hypamentioning
confidence: 99%
See 1 more Smart Citation